A STUDY ON THE DIFFICULTIES IN TRANSLATING COLLOCATIONS FROM ENGLISH TO VIETNAMESE DURING THE TRANSLATION LEARNING PROCESS OF THIRD-YEAR ENGLISH MAJOR STUDENTS AT DONG A UNIVERSITY - Võ Thị Thanh Trúc, Võ Thị Thanh Trúc; Nguyễn Hồ Thúy Vy, Nguyễn Hồ Thúy Vy (Tạp chí Khoa học Đại học Đông Á, 2025)
This study investigates the challenges faced by third-year English majors at Dong A University in translating English collocations into Vietnamese. Emphasizing the role of collocations in natural and accurate translation, the study identifies common difficulties, types of collocation they often make mistakes, and the strategies they use when finding suitable Vietnamese equivalents. The study adopts a quantitative approach, gathering data from a survey completed by 76 students. The findings indicate that students frequently encounter difficulties in accurately interpreting the meanings of collocations and selecting suitable Vietnamese equivalents, particularly in cases involving prepositional combinations. Based on the results, the study recommends that teachers incorporate more collocation-focused exercises in translation lessons, provide real-life examples, and guide students in using reliable tools.